QUALITY OF STORAGE OF EXPRESSED MILK TO ITS DESTINATION IN THE APL LÁCTEO OESTE GOIANO - Gabrielle Borges Cruvinel, Kellita; Gomes Pereira, Matheus; José Gonçalves dos Santos, Klayto (Journal of Interdisciplinary Debates, 2025)
Dairy farming in Brazil has increased significantly in the last decade, an advance that has boosted production and made the country one of the leading countries in this sector. Milk quality is strictly related to the degree of initial contamination and the time and temperature that the milk is retained after milking until processing. The hygienic conditions under which milk is obtained and stored have a significant impact on its quality, as well as on its transport to further processing in the dairy industry. The objective of this study was to analyze the growth of milk production in the state context of Goiás, as well as its consumption, and storage parameters until it arrives at the dairy for its proper processing. To carry out this study, a field research methodology was used, with interviewed producers who are included in the Western Goiás region, located in 24 municipalities. The results obtained for the total number of producers per daily production, in response to the group of researched, of a total of 450 rural producers in the dairy activity, among the small and medium producers, 276 have expansion tanks for cooling the milk in their own headquarters, in response to this, the 174 producers, who do not have their own tanks, It makes use of communal tanks for the delivery and storage of milk. Thus, milk quality, being one of the most discussed issues within milk production, good practices are necessary to ensure the safety of the consumer of the final product, and the lack of verification of reports of the portion of producers who do not receive the milk quality report, is also linked to the factors of withdrawal from the activity.